ANALISIS LAYANAN FASILITAS TERMINAL PENGGARON SEMARANG TERHADAP KEPUASAN PENGGUNA DENGAN METODE IMPORTANCE PERFOMANCE ANALYSIS (IPA) - Navis, Ahmad Akbar; Rizani, Mohammad Debby; Yudaningrum, Farida (Universitas PGRI Semarang, 2023)
Penggaron Terminal is a type B terminal in the Pedurungan District area which serves departments such as Mangkang, Karang Ayu, Solo, Wonosobo, Kebumen, Cepu, Purwodadi, and cities or regencies within the province of Central Java. This research aims to determine the level of service at the Penggaron terminal using the importance performance analysis (IPA) method. This research was conducted at the Penggaron type-B terminal for two weeks, the first week the questionnaires were distributed to respondents on Mondays and Sundays in the morning at 07:00-10:00 WIB and in the afternoon at 16:00-18:00 WIB. This research is included in the quantitative research with a descriptive research approach. Data collection uses primary data, namely data obtained from the answers of the respondents to the questions posed by the researcher. Secondary data from literature study in the form of documents, laws and regulations, journals, scientific papers, supporting data relating to the problem under study. Based on the results of data analysis and processing using the Importance Performance Analysis (IPA) method in the Cartesian diagram, the service facilities at the Penggaron bus terminal are dominant in quadrant 2, which shows high expectations and reality, and quadrant 4, which means expectations of low use and high reality. However, there are a small number of service facilities that are in the quadrant, which means that the expectations from users are high but the reality is low. So, based on user evaluation, the service at the Penggaron terminal is quite good.